Chemical characterization, hardness and termite resistance of Quercus cerris heartwood from Kosovo - Bajraktari, A.; Nunes, L.; Knapic, S.; Pimenta, R.; Pinto, T.; Duarte, S.; Miranda, I.; Pereira, H. (Maderas. Ciencia y Tecnología, 2018)
Quercus cerris, the Turkey oak, is an oak species native to southern central and southeastern Europe, extending into southwestern Asia. It is present in a large extent in the forests of the Republic of Kosovo, and at present used mainly for bio-energy. The potential use of Q. cerris wood for construction and higher value wood products has been investigated in the last years. However limited information is available on wood characteristics and performance, mainly regarding chemical composition and durability. The heartwood of Q. cerris taken from 70-90 year-old trees grown in two sites in Kosovo was studied regarding resistance to termite attack, chemical composition and hardness. The heartwood contained only 6.7% extractives, with a small content of tannins. The wood density was on average 0.81 at 12% moisture content and Brinell hardness 36.2 N mm-2. It was classified as not durable against subterranean termites and therefore not suitable for external use in ground contact in termite areas unless adequately protected. Nevertheless, Q. cerris wood showed adequate hardness and density for interior uses like flooring for domestic and commercial applications with moderate use.